Restoring fire-prone Inland Pacific landscapes: seven core principles - Hessburg, Paul F; Churchill, Derek J; Larson, Andrew J; Haugo, Ryan D; Miller, Carol; Spies, Thomas A; North, Malcolm P; Povak, Nicholas A; Belote, R. Travis; Singleton, Peter H; Gaines, William L; Keane, Robert E; et al. (Landscape ecology, 2015)
CONTEXT: More than a century of forest and fire management of Inland Pacific landscapes has transformed their successional and disturbance dynamics. Regional connectivity of many terrestrial and aquatic habitats is fragmented, flows of some ecological and physical processes have been altered in space and time, and the frequency, size and intensity of many disturbances that configure these habitats have been altered. Current efforts to address these impacts yield a small footprint in comparison to wildfires and insect outbreaks. Moreover, many current projects emphasize thinning and fuels reduction within individual forest stands, while overlooking large-scale habitat connectivity and disturbance flow issues. METHODS: We provide a framework for landscape restoration, offering seven principles. We discuss their implication for management, and illustrate their application with examples. RESULTS: Historical forests were spatially heterogeneous at multiple scales. Heterogeneity was the result of variability and interactions among native ecological patterns and processes, including successional and disturbance processes regulated by climatic and topographic drivers. Native flora and fauna were adapted to these conditions, which conferred a measure of resilience to variability in climate and recurrent contagious disturbances. CONCLUSIONS: To restore key characteristics of this resilience to current landscapes, planning and management are needed at ecoregion, local landscape, successional patch, and tree neighborhood scales. Restoration that works effectively across ownerships and allocations will require active thinking about landscapes as socio-ecological systems that provide services to people within the finite capacities of ecosystems. We focus attention on landscape-level prescriptions as foundational to restoration planning and execution.